Ett nytt växtsortiment : för inglasade miljöer - Eriksson, Pontus (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2006)
A new project has developed at the Swedish University of Agricultural Sciences in Alnarp during the spring of 2006. The garden design students has, during the course Interior Garden Design designed and built an construction with a new range of plants for Swedish conservatories. The plants are mainly from the cool temperate areas, instead of the tropical which often are the most common in public spaces. This means, among other things, that the cost for warming is very low. The working process and the construction carried on as workshops in the conservatory at Trädgårdslaboratoriet in Alnarp. During a few weeks the hole construction is completed. After some month the result are over all expectations. The plants has established very well and grown a lot in a short time. The future for the new range of plants looks bright. The plants are easy to find on the market. On thing to do is to get out the knowledge on the market and establish the new niche. One similar project are already existing in Malmö, Glasbubblan at the Västra Hamnen which were completed in early 2006. This essay is a report, which includes a story and disuses fact of the plants. You also find many photos of the plants and construction. The meaning of these photos is to, in an illustrative and creative way, show interior garden design.